2019
DOI: 10.3390/ijms20051041
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Analysis of miRNA and mRNA Expression Profiles in Spleen of Specific Pathogen-Free Chicken Infected with Avian Reticuloendotheliosis Virus Strain SNV

Abstract: The Reticuloendotheliosis virus (REV) primarily causes avian severe immunosuppression, in addition to other symptoms, which include avian dwarfing syndrome and chronic tumors in lymphoid and other tissue. To date, REV’s molecular mechanisms leading to immunosuppression have not been fully elucidated. In the current study, we aimed to elucidate the role of microRNAs (miRNA) in regulating gene expression during REV infections. Therefore, we used a high-dose spleen necrosis virus (SNV) model of REV to inoculate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 50 publications
3
7
0
Order By: Relevance
“…Additionally, gga-miR-200-3p was expressed in high abundance between 14 weeks and 22 weeks, and it also targeted TGFB3 related to TGFbeta signaling pathway and MAPK signaling pathway in abdominal adipose tissue during postnasal late development [18]. In response against Reticuloendotheliosis Virus, gga-miR-200a-3p was negatively correlated with CTLA4, a negative regulator of T cell activation in spleen [19]. Interestingly, gga-miR-200a-3p was found to be significantly up-regulated in the susceptible line 7.2 compared to the resistant line 6.3 in response to Necrotic Enteritis in our previous study [20].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, gga-miR-200-3p was expressed in high abundance between 14 weeks and 22 weeks, and it also targeted TGFB3 related to TGFbeta signaling pathway and MAPK signaling pathway in abdominal adipose tissue during postnasal late development [18]. In response against Reticuloendotheliosis Virus, gga-miR-200a-3p was negatively correlated with CTLA4, a negative regulator of T cell activation in spleen [19]. Interestingly, gga-miR-200a-3p was found to be significantly up-regulated in the susceptible line 7.2 compared to the resistant line 6.3 in response to Necrotic Enteritis in our previous study [20].…”
Section: Introductionmentioning
confidence: 99%
“…Among these 66 know SDE miRNAs, 12 miRNAs (miR-22-3p, miR-22-5p, miR-30e-5p, miR-31-5p, miR-32-5p, miR-33-5p, miR-92-5p, miR-155, miR-184-3p, miR-215-5p, miR-451 and let-7b) are also found to be differentially expressed in chicken lungs, immune organs, and embryo fibroblasts during H5N3, H5N1 and H9N2 AIV infection [ 5 , 16 , 17 ]. In addition, another 7 know SDE miRNAs (miR-7, miR-21-3p, miR-34c-5p, miR-187-3p, miR-200a-3p, miR-429-3p and miR-1434) are identified in other virus infected chickens [ 18 20 ]. Therefore, these DE miRNAs might play a vital role in the interaction between chicken DCs and H9N2 AIV.…”
Section: Discussionmentioning
confidence: 99%
“…The poultry immune system is also activated by REV, leading to differential miRNA expression in the host. Gao et al identified 27, 29, and 29 DE-miRNAs in the spleen of in vivo REVinfected chickens at 7, 14, and 21 days post-infection, respectively (165). The authors demonstrated a negative correlation between 14 miRNAs (miR-200a-3p, miR-375, miR-1458, miR-1664-3p, miR-122-5p, miR-222b-5p, miR-147, miR-1329-5p, miR-1618-5p, miR-1664-3p, miR-146b-3p, miR-222b-3p, miR-144-3p, and miR-1769-3) and 14 target genes, all of which were involved in a variety of biological pathways, including the endocrine system, the immune system, cell growth, and cell death (165).…”
Section: The Endocrine System and Its Response To Stressmentioning
confidence: 99%